Comparison of Relative Loudness Judgment in Children using Listening Devices with Typically Developing Children - Tak, Shubha; Yathiraj, Asha (International Archives of Otorhinolaryngology, 2020)
Introduction Loudness perception is considered important for the perception of emotions, relative distance and stress patterns. However, certain digital hearing devices worn by those with hearing impairment may affect their loudness perception. This could happen in devices that have compression circuits to make loud sounds soft and soft sounds loud. These devices could hamper children from gaining knowledge about loudness of acoustical signals.Objective To compare relative loudness judgment of children using listening devices with age-matched typically developing children.Methods The relative loudness judgment of sounds created by day-to-day objects were evaluated on 60 children (20 normal-hearing, 20 hearing aid users, & 20 cochlear implant users), utilizing a standard group comparison design. Using a two-alternate forced-choice technique, the children were required to select picturized sound sources that were louder.Results The majority of the participants obtained good scores and poorer scores were mainly obtained by children using cochlear implants. The cochlear implant users obtained significantly lower scores than the normal-hearing participants. However, the scores were not significantly different between the normal-hearing children and the hearing aid users as well as between the two groups with hearing impairment.Conclusion Thus, despite loudness being altered by listening devices, children using non-linear hearing aids or cochlear implants are able to develop relative loudness judgment for acoustic stimuli. However, loudness growth for electrical stimuli needs to be studied.
Keywords: relative loudness perception; cochlear implants; non-linear hearing aids